1989
DOI: 10.1172/jci114329
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of rhinitis. Lactoferrin and lysozyme in nasal secretions.

Abstract: The antimicrobial proteins lactoferrin (Lf) and lysozyme (Ly)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
3

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(111 citation statements)
references
References 27 publications
6
102
3
Order By: Relevance
“…It is a product of glandular processes in the nasal mucosa. 23 Interestingly, in agreement with the present study, lactotransferrin in serum was recently found to be inversely associated with allergic rhinitis caused by mites. 24 A number of other proteins with antimicrobial activities were detected with significantly changed expression in one or several of the study groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is a product of glandular processes in the nasal mucosa. 23 Interestingly, in agreement with the present study, lactotransferrin in serum was recently found to be inversely associated with allergic rhinitis caused by mites. 24 A number of other proteins with antimicrobial activities were detected with significantly changed expression in one or several of the study groups.…”
Section: Discussionsupporting
confidence: 93%
“…Lactotransferrin is an iron-binding transport protein with antimicrobial properties 23 which probably take part in the host defense. It is a product of glandular processes in the nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The inferior nasal turbinates are rich in submucosal glands, which secrete copious amounts of fluid and mucus to humidify inspired air and trap particles and pathogens. Functional and histological studies have not revealed any significant differences between nasal submucosal glands and those found in lower airways (16,(33)(34)(35)(36)(37), and intact human nasal glands also exhibit CFTR-dependent fluid secretion in response to [cAMP] i -elevating agonists (16,37).…”
Section: Low [Vip] Potentiates Cftr-dependentmentioning
confidence: 97%
“…The remaining supernatant was frozen at -20 o C until biochemical analysis. Biomarkers analyzed included eosinophil cationic protein (ECP), which is a marker of eosinophil activity (Venge et al, 1987), myeloperoxidase (MPO) from neutrophils in the mucosa (Venge, 1994), lysozyme a marker of neutrophil activity and secretion from parasympathetically innervated mucosal glands (Raphael et al, 1989), and albumin, which is a marker of capillary leakage of plasma proteins (Raphael et al, 1991). Analyses of ECP, MPO and lysozyme were made by radio-immunoassays (RIA) and albumin by nephelometry at the University Hospital of Uppsala.…”
mentioning
confidence: 99%